2015
DOI: 10.1149/2.0801504jes
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Over-Lithiated Layered Oxides with PEDOT:PSS Conducting Polymer in Lithium-Ion Batteries

Abstract: Over-lithiated layered oxide (OLO) materials were coated with a PEDOT:PSS conducting polymer via a simple wet-coating method. The prepared samples were observed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). The electrochemical properties of the samples were determined by galvanostatic testing and electrochemical impedance spectroscopy (EIS). PEDOT:PSS coated cathode materials showed better rate capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…At charge/ discharge current density of 0.1/0.1 C, the areal capacity of the 450 ”m (= 8 sheets) HM OLO cathode was 13.0 mAh cm cathode −2 , which is a remarkably high value that corresponds to stripping/ plating of a lithium metal layer with a thickness of 65 ”m. [ 52 ] Notably, Figure 3 c also presents that the areal capacity of the 450 ”m HM OLO cathode is approximately 6 times higher than those of the previously reported results, [ 33,46,53,54 ] underscoring the electrochemical superiority of the heteronanomat architecture. The cycling performance of the multistacked HM OLO cathodes was examined at charge/discharge current density of 0.5/0.…”
Section: B)mentioning
confidence: 60%
See 1 more Smart Citation
“…At charge/ discharge current density of 0.1/0.1 C, the areal capacity of the 450 ”m (= 8 sheets) HM OLO cathode was 13.0 mAh cm cathode −2 , which is a remarkably high value that corresponds to stripping/ plating of a lithium metal layer with a thickness of 65 ”m. [ 52 ] Notably, Figure 3 c also presents that the areal capacity of the 450 ”m HM OLO cathode is approximately 6 times higher than those of the previously reported results, [ 33,46,53,54 ] underscoring the electrochemical superiority of the heteronanomat architecture. The cycling performance of the multistacked HM OLO cathodes was examined at charge/discharge current density of 0.5/0.…”
Section: B)mentioning
confidence: 60%
“…c) Charge/discharge capacities per cathode area (mAh cm cathode −2 ) of multistacked HM OLO cathodes, wherein discharge capacities of the previously reported OLO cathodes were marked by star symbols (pink, [ 31 ] blue, [ 45 ] green, [ 53 ] black. [ 54 ] The cycling performance of the 8 sheets-stacked HM LNMO cathode was examined using a half cell (HM LMNO cathode/ Li metal anode), where the cell was cycled at charge/discharge current density of 0.2/0.2 C under voltage range of 3.50-4.95 V. Even at such harsh operating condition (i.e., ultrathick (= 420 ”m) cathode and high charging voltage (= 4.95 V)), the HM LNMO cathode showed good cycling performance (capacity retention after 30 cycles = 78.5%, Figure 4 f), although its capacity retention was slightly lower than that of thinner HM LNMO cathodes. Future works will be devoted to further improving the capacity retention with cycling.…”
Section: B)mentioning
confidence: 99%
“…It is highly likely that the slightly high capacity retention capability of the surface modified OLO originates from the reduction of electrolyte decomposition due to the protective coating layer of a -CoPO 4 on the surface of OLO particles. The phenomenon of voltage decay and degradation of electrodes in fact are very typical electrochemical trends for high manganese based lithium rich materials due to their structural transformation to spinel like structure, thereby lowering energy density during extended cycling2232. The ex-situ STEM EDAX (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They also reported that wetting the fabricated cathode with vanadium precursor solution to facilitate the impregnation of VO x into the layered structure also results in enhanced electrode stability19. Furthermore, several studies reported that surface modification of OLO nanocomposite cathodes with various materials such as self-catalyzed Polyaniline (PANI)20, lithium conductive Li 2 TiF 6 21, and Poly (3, 4-ehtylenedioxythiophene) Polystyrene sulfonate (PEDOT: PSS) led to the improvement of electrode performance and stability22.…”
mentioning
confidence: 99%
“…Because conductive polymers can interact synergistically with inorganic compounds, the electrode lifetime, rate capability, thermal stability, etc. are greatly improved [113]. Mantione et al [114] PEDOT:PSS ((poly(3,4-ethylenedioxythiophene) polystyrene sulfonate)) has a promising rate capability and cyclability between 2.0 V and 4.6 V. Kim et al [115,116] found that polymer-coated LiCoO 2 delivered a significant improvement in electrochemical performance and thermal stability of lithiumion batteries compared with bare LiCoO 2 and that coated with Al 2 O 3 (Fig.…”
Section: Conductive Polymer Surface Modificationmentioning
confidence: 99%